Comparison of survey data on wealth in Switzerland - Ravazzini, Laura; Kuhn, Ursina; Brulé, Gaël; Suter, Christian (My University, 2019)
Beyond income, wealth is one of most relevant components among national and international indicators of household finances. Three surveys that include Switzerland have recently integrated questions about wealth and its components. These surveys are the Swiss Household Panel -SHP- (2016), the Statistics on Income and Living Conditions -CH-SILC- (2015), and the Survey on Health, Ageing and Retirement in Europe -SHARE- (2015). Following three important criteria suggested by the Organisation for Economic Co-operation and Development (OECD), namely relevance, coherence and accuracy, this study systematically compares data on housing and financial wealth. The analysis addresses question wording, the comparison with national accounts and accuracy. Results suggest that SHARE is the most relevant survey in terms of financial wealth and total net worth. CH-SILC is a coherent survey that allows for additional analysis on subjective living conditions, while the SHP is an ecological survey in terms of the number of questions on wealth.
Keywords: wealth; survey data; real estate; financial assets; data quality